2019
DOI: 10.1186/s13287-019-1366-y
|View full text |Cite
|
Sign up to set email alerts
|

Human amniotic mesenchymal stem cells and their paracrine factors promote wound healing by inhibiting heat stress-induced skin cell apoptosis and enhancing their proliferation through activating PI3K/AKT signaling pathway

Abstract: Background: Increasing evidence has shown that mesenchymal stem cells (MSCs) yield a favorable therapeutic benefit for thermal burn skin wounds. Human amniotic MSCs (hAMSCs) derived from amniotic membrane have multilineage differentiation, immunosuppressive, and anti-inflammatory potential which makes them suitable for treating skin wounds. However, the exact effects of hAMSCs on the healing of thermal burn skin wounds and their potential mechanisms are not explored. Methods: hAMSCs were isolated from amniotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
139
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(147 citation statements)
references
References 73 publications
(82 reference statements)
4
139
0
Order By: Relevance
“…Gsk3β is a typical regulation of the negative Wnt signaling pathway. Many researchers have described PI3K/AKT and Gsk3β/β-catenin signals as playing a key role in skin development and wound healing [44]. Based on the findings of previous studies, Gsk3β/β-catenin and PI3K/Akt signaling pathway was selected for verification.…”
Section: Discussionmentioning
confidence: 99%
“…Gsk3β is a typical regulation of the negative Wnt signaling pathway. Many researchers have described PI3K/AKT and Gsk3β/β-catenin signals as playing a key role in skin development and wound healing [44]. Based on the findings of previous studies, Gsk3β/β-catenin and PI3K/Akt signaling pathway was selected for verification.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a D-gal-induced decline in Akt phosphorylation was also found in human umbilical vein endothelial cells [46]. Recently, Li et al reported that human amniotic MSCs e ciently ameliorate heat stress-induced skin injury by inhibiting apoptosis in skin cells through activating the Akt signaling pathway [47]. Based on these studies, we hypothesized that Akt/GSK-3β/Fyn pathway is involved in hPMSCs induced Nrf2 activation in senescent CD4 + T cells.…”
Section: Discussionmentioning
confidence: 58%
“…Similarly, a D-gal-induced decline in Akt phosphorylation was also found in human umbilical vein endothelial cells [45]. Recently, Li et al reported that human amniotic MSCs e ciently ameliorate heat stress-induced skin injury by inhibiting apoptosis in skin cells through activating the Akt signaling pathway [46]. Based on these studies, we hypothesized that Akt/GSK-3β/Fyn pathway is involved in hPMSCs induced Nrf2 activation in senescent CD4 + T cells.…”
Section: Discussionmentioning
confidence: 58%